The Admission Decision Support System for Muhammadiyah Student Association Cadres Using the Profile Matching Method - Rusydi Umar; Anton Yudhana; Jaka Dernata (JUITA : Jurnal Informatika, 2022)
Technological advances are beneficial for humans in doing work, one of which is that technology can help humans make decisions. Muhammadiyah Student Association is a large organization. The establishment of this organization continues to have progress to make many students join the organization.  With many students who want to join, the organization has difficulty determining the eligibility of each prospective member who wants to join because the organization must pay attention to factors that can support the assessment in the acceptance of its members. This research aims to conduct the selection process of organizational members using profile matching methods to help the organization solve the problems faced by making the right decision. Then the result obtained is a decision that follows the organization's expectations in the selection of new prospective members. The assessment used in this method consists of four aspects, two of which are core factors and two other aspects are secondary factors. The data processing results will become a ranking format so that this method can also determine the best candidate members based on ranking.